Association between overweight/obesity and multidrug-resistant tuberculosis - Peinado, Jesus (2023)
Purpose: Globally, transgender women (TGW) experience wide-ranging barriers to health and care, with disproportionately high risks of infectious and chronic diseases. Yet, research on transgender populations' access to care in low- and middle-income countries remains limited, focused on human immunodeficiency virus (HIV) infection, and assesses TGW as a homogenous group. We analyzed morbidity and health service uptake patterns among TGW in Lima, Perú, to understand health outreach and service needs to inform targeting and design of community-level interventions. Methods: This cross-sectional study surveyed a convenience sample of 301 TGW in metropolitan Lima during September-October 2020. We report descriptive statistics and bivariable and multivariable regression model results as adjusted prevalence ratios (aPRs). Results: Health coverage and access to care were suboptimal. Less education and older age were positively associated with illness and negatively associated with HIV and tuberculosis (TB) testing. In the first study to quantitatively examine health utilization by gender identity subgroup (i.e., woman, trans or transgender, transsexual, “transformista,” “travesti,” and other) in Perú, TGW who identified as women were more likely to ever test for HIV (aPR = 1.49, 95% confidence interval [CI]: 1.16-1.91) and use pre-exposure prophylaxis (PrEP) (aPR = 2.36, 95% CI: 1.15-4.80). Both awareness and interest regarding PrEP were low, as was usage among those who were interested in taking PrEP. Conclusion: Public health efforts should be tailored to meet TGW's diverse needs, expand TB testing, bridge the gap between PrEP interest and use, and increase insurance coverage and access to trans-friendly services for improved health.